Intellectual Capital Disclosure of Muhammadiyah Universities: Evidence from 4ICU 2018 - Ihyaul Ulum; Pratiwi Fitri Wijayanti (Journal of Accounting and Investment, 2019)
This study aimed to identify the practice of disclosure on intellectual capital (IC) information on the website of Muhammadiyah Universities in Indonesia. This study used the 44 websites of best Muhammadiyah universities (version 4 International Colleges and Universities survey 2018) as the samples of study. Intellectual capital components used in this study were a framework constructed by Ulum (2012), which consists of 46 items: 8 items on human capital, 23 items on structural capital, and 15 items on relational capital. The research method used was content analysis. The results showed that from the 44 websites of Muhammadiyah Universities, the IC information which was in form of a narrative was 16%, the figure was 8%, the currency (rupiah) was 0.15%, and the graph was 0.75%. From the 44 Muhammadiyah Universities, none of them revealed the information completely, and it is proved low disclosure of intellectual capital in the website. In terms of the amount of information disclosed, on the average, Muhammadiyah Universities tended to reveal information in forms of narrative format.